Code Switching and Code Mixing on “Ngobrol Sore Semaunya” Podcast - Agathar Narulia Sekar Langit; Isti'anatul Hikmah; Dita Surwanti (University of Darussalam Gontor, 2022)
This study focused on finding the types and the reasons behind the use of code switching and code mixing on “Ngobrol Sore Semaunya” podcast. This study is aimed to answer these following questions (1) What are the types of code switching and code mixing found on